ORMDL3 is associated with airway remodeling in asthma via the ERK/MMP-9 pathway - Yu, Fei (Mol Med Rep, 2017)
ORMDL sphingolipid biosynthesis regulator 3 (ORMDL3) has been previously implicated in asthma pathogenesis, its effect on airway remodeling remains to be elucidated. The present study examined the expression levels of ORMDL3 in a mouse model of asthma. Mice were divided into three groups: Asthmatic model (n=10), budesonide-treated (n=10) and a control group (n=8). Asthma was induced by sensitization with ovalbumin (OVA) and aluminum hydroxide on day 1, 7 and 14. Subsequently mice were exposed to OVA three times per week from day 28. In order to investigate the mechanism of airway remodeling 100 µg/kg aerosol budesonide was administered to 6 animals prior to exposure to OVA. The condition of lung tissues was assessed through histology, and the expression levels of ORMDL3, phosphorylated-extracellular-signal regulated kinase (p-ERK) and matrix metallopeptidase-9 (MMP-9) were quantified using immunohistochemistry, reverse transcription-quantitative polymerase chain reaction and western blotting. A severe inflammatory response and airway remodeling were pretreatment with budesonide. Expression levels of ORMDL3, phosphorylated (p)-ERK and MMP-9 were significantly greater in the asthma-model group; however, in the group pretreated with budesonide their expression was reduced. Expression levels of ORMDL3, p-ERK and MMP-9 were significantly positively correlated with bronchial wall thickness. ORMDL3 expression was significantly positively correlated with p-ERK and MMP-9. Therefore, increased ORMDL3 expression may induce the p-ERK/MMP-9 pathway to promote pathological airway remodeling in patients with asthma.